Cultivation and characteristics of aerobic granular sludge for simultaneous organics and nutrients removal performances at high temperature - Ab. Halim, Mohd. Hakim (2014)
With inoculum sludge from a conventional activated sludge wastewater treatment plant, a sequencing batch reactor fed with synthetic wastewater was operated at 50 ± 1 °C to study the formation of aerobic granular sludge (AGS) for simultaneous organics and nutrients removal with a complete cycle time of 3 h. The AGS were successfully cultivated with excellent settling ability and demonstrated exceptional performance in the organics and nutrients removal with influent loading rate and COD/N ratio of 1.6 kg COD (L.d)-1 and 8.3, respectively. Stable, regular, dense and fast settling granule (average diameter, 2.0 mm and settling velocity, 26 m h-1) were developed in a single reactor. In addition, 76% COD removal efficiency was observed in the system at the maturation stage of the granulation, while its ammonia and total phosphorus removal efficiencies were up to 88% and 69%, respectively. The study demonstrated the capabilities of AGS formation in a single, high and slender column type-bioreactor at high temperature which is suitable to be applied for hot climate and low humidity condition (e.g. Saudi Arabia).